The impacts of organization culture and job satisfaction on turnover intention in the fast food retail industry in Malaysia - Buhari Kabir Khalil
One of the performance measures of fast-food restaurants' supervisor was employee's job turnover within the organization where the turnover rate of less than 80% was regarded as good performance during a fiscal year. Recently, previous studies noted that employees' job turnover rate in the fast-food restaurant had increased. Previous studies also illustrated that appropriate attention was not given to address the problem of employees' job turnover especially within the context of fast-food industry in Malaysia. Efforts should be undertaken to determine the predicting factors that affect employees' job turnover in order to reduce the turnover rate. Therefore, this study was conducted to investigate the impact of organization culture and employees' job satisfaction on employees' job turnover intention within the fast food industry in Malaysia. Specifically, the objectives of the study are to i) determine the influence of organization culture on employees' turnover intention, ii) examine the influence of organization culture on job satisfaction, iii) assess the influence of job satisfaction and turnover intention and iv) determine the mediating role of job satisfaction on the relationship between organization culture and employee turnover intention. A total of 299 questionnaires distributed to employees of fast food restaurants within Klang valley in Malaysia, where 269 questionnaires were returned (93.4%) were returned. Out of the returned 269 questionnaires, 260 were found good and selected for the analysis. The fast food outlets were selected using random sampling method. The data was analyzed by Structural Equation Modelling (SEM) using Statistical Package for Social Sciences (SPSS) to test the proposed hypotheses. The findings of the study revealed that i) organization culture significantly influenced employees' job turnover intention, ii) organization culture significantly influenced employees' job satisfaction, iii) employees' job satisfaction has a significant influence on turnover intention and finally, iv) job satisfaction mediate the relationship between organization culture and turnover intention. The findings of this study provide significant contributions to the fast food industry in Malaysia especially in terms of formulating strategies to enhance organization culture and employee job satisfaction in the effort to reduce employees' job turnover intention.